Metal Ion Toxins and Brain Aquaporin-4 Expression: An Overview - Ximenes-da-Silva, Adriana (Frontiers in Neuroscience, 2016)
Metal ions such as iron, zinc, and manganese are essential to metabolic functions, protein synthesis, neurotransmission, and antioxidant neuroprotective mechanisms. Conversely, non-essential metals such as mercury and lead are sources of human intoxication due to occupational activities or environmental contamination. Essential or non-essential metal accumulation in the central nervous system (CNS) results in changes in blood-brain barrier (BBB) permeability, as well as triggering microglia activation and astrocyte reactivity and changing water transport through the cells, which could result in brain swelling. Aquaporin-4 is the main water channel in the CNS, is expressed in astrocyte foot processes in brain capillaries and along the circumventricular epithelium in the ventricles, and has important physiological functions in maintaining brain osmotic homeostasis and supporting brain excitability through regulation of the extracellular space. Some evidence has pointed to a role of AQP4 during metal intoxication in the brain, where it may act in a dual form as a neuroprotector or a mediator of the development of oxidative stress in neurons and astrocytes, resulting in brain swelling and neuronal damage. This mini-review presents the way some metal ions affect changes in AQP4 expression in the CNS and discuss the ways in which water transport in brain cells can be involved in brain damage.